Pateo do Collegio: um lugar na cidade de São Paulo - Fortunato, Ivan [UNESP] (2014)
The Pateo do Collegio, at the heart of São Paulo Historic Downtown, is recognized as the founding place of the city of São Paulo. Located at the hill of the Piratininga Plateau, it was discovered in the sixteenth century by the priests of the Society of Jesus, who set school and church in the place, naming the village of São Paulo Piratininga in Mass celebrated at January 25, 1554. We have met the place by chance, when a sudden sense of enchantment led us to want to know it better. From the hypothesis that its geographicity allows us to classify it as an ontological place, this thesis aimed to uncover its essence and demonstrate the sense of this place in its historical, cultural, built, telluric and symbolic aspects. Epistemologically grounded in Humanistic Geography, we have developed our thesis by the presence in the place, observing, talking to people, drawing maps, photographing, but also checking the literature and historical records... the main intention was the gathering of meanings and values about this iconic place. In the end, this geopoetics gave us the prerogative to name the Pateo do Collegio as a living place in São Paulo, qualified by very private historicity and geographicity, as being the place where the city was born, raised and expanded, from village to metropolis...